Effect of cotton seed oil methyl ester on the performance and exhaust emission of a diesel engine - Yücesu, HS; Ilkiliç, C (Taylor & Francis Inc, 2006)
Numerous studies indicated that oil sources in the world will come to an end. As a result, new alternative energy sources will be required to substitute for oil. Some of the experimental studies showed that vegetable oil can be used as alternative fuel in diesel engines. The viscosity of vegetable oil is much higher than that of standard diesel fuel; therefore, the high viscosity of the vegetable oil can cause problems for injection systems and engine components. To decrease viscosity, cottonseed methyl ester was obtained from raw cottonseed oil by transesterification method. In this study, cottonseed methyl ester was used in a four-stroke, single cylinder, and air-cooled diesel engine as alternative fuel. Engine tests carried out at full load-different speed range, the engine torque and power of cottonseed oil methyl ester was found to be lower than that of diesel fuel in the range of 3-9% and specific fuel consumption was higher than that of diesel fuel by approximately 8-10%. CO2, CO, and NOx emissions of cottonseed methyl ester were lower than that of diesel fuel.
Keywords: alternative fuel; cottonseed methyl ester; diesel engine; engine performance; exhaust emission